Guzmania altomayoensis (Bromeliaceae): a New Species from Peru related to Guzmania striata L.B.Sm. - Gouda, Eric J. (Phytotaxa, 2025)
A new Guzmania species from Peru, G. altomayoenis is described, illustrated and compared to the morphologically closely related species Guzmania striata from Ecuador. This plant is in culture for many years at the nursery of Jeffrey Kent in Vista, California, and recently at Anthura in Bleiswijk, the Netherlands. A specimen has been on loan at the Botanic Garden Utrecht to prepare this publication and preserve herbarium material for the type specimens.